School Well-Being and Drug Use in Adolescence - Santibáñez, Rosa; Solabarrieta, Josu; Ruiz-Narezo, Marta (Frontiers in Psychology, 2020)
This research is part of the last study Drugs and School IX developed in the Basque Country (Spain) by the Instituto Deusto de Drogodependencias (Deusto Institute of Drug Addiction) of the University of Deusto and the data gathered by means of cluster sampling in two stages. The sample is made up of N= 6.007 girls and boys ranging from 12 to 22 years of age in Secondary Education and the aim is to answer the following new research questions based on those parameters: (1) describe the reality of drug consumption and some psychosocial variables in this sample, as well as analyse several relations between variables; (2) analysing the role of school well-being, self-esteem and self-concept regarding consumption; (3) taking a close look at the moderating role of age and gender on the relationship of school well-being, self-concept and self-esteem with consumption; and (4) understand the existing interaction between all these variables, studying the moderating role of self-esteem and self-concept in the influence of school well-being on consumption. Using a correlation, hierarchical regression and mediation analysis with SPSS (v. 26) and Amos (v. 26) applications, three main conclusions were reached. Firstly, that educational and academic well-being, academic self-concept and self-esteem seem to play the role of protecting factors in adolescence, while assertiveness is linked to a higher consumption level. Secondly, that academic self-concept has a mediating effect between well-being and consumption. Some of these relations are moderated by the variables of gender and age. Thirdly, that age and gender are very relevant sociodemographic variables that must be taken into account in order to understand this phenomenon. Age has shown its covariant effect, which is especially relevant in the influence of academic well-being measured as being held back years. It has also proved to be important in order to understand its experiential or experimental and transitory character. Moreover, significant differences in consumptions have been found based on gender.